Intraventricular or intrathecal colistin for the treatment of central nervous system infections caused by multidrug-resistant Gram-negative bacteria. Issue 4 (April 2014) - Imberti, Roberto; Iotti, Giorgio Antonio; Regazzi, Mario
<x xml:space="preserve">Abstract</x> Central nervous system infections caused by Gram-negative bacteria susceptible only to colistin are rare but life-threatening and increasing in prevalence. Given the current antibiotic development pipeline it is likely that the paucity of therapeutic options will continue for the next years. Colistin is an amphipathic bactericidal antibiotic which is administered systemically as colistin methanesulfonate (also known as colistimethate sodium). Colistin methanesulfonate is the inactive prodrug, and in cerebrospinal fluid undergoes spontaneous hydrolysis to colistin (the active form with antimicrobial activity). In this review, we describe and evaluate the clinical and experimental data supporting the use of intraventricular (IVT) or intrathecal (IT) colistin against multidrug-resistant Gram-negative infections of the central nervous system, describe the permeability of the blood-brain barrier to colistin, the pharmacokinetics of colistin after IVT administration of colistin methanesulfonate, its anti-endotoxin activity, discuss the opportunity to administer colistin intraventricularly or intrathecally and the dose regimen, and provide recommendations based on the available evidence.